Generation of Cryptographic Keys with Algorithm of Polygon Triangulation and Catalan Numbers - Saračević, Muzafer; Selimi, Aybeyan; Selimovic, Faruk (Computer Science, 2018)
In this paper is presented a procedure for the application of one computational geometry algorithm in the process of generating hidden cryptographic keys from one segment of the 3D image. The presented procedure consists of three phases. In the first phase, is done the separation of one segment from the 3D image and determination of triangulation of the separated polygon. In the second phase, is done a conversion from the obtained triangulation of the polygon in the record which represent the Catalan key. In the third phase, the Catalan-key is applied in encryption of text based on the balanced parentheses combinatorial problem.